Developing local extension capacity - Digital Green (International Food Policy Research Institute, 2019)
The Feed the Future Developing Local Extension Capacity (DLEC) project galvanizes diverse extension and advisory service (EAS) stakeholders to measurably improve agricultural extension programs, policies and services.